High resolution satellite imaging 0.5U-size freeform telescope for CubeSat - Wojtanowski, Jacek (Advanced Optical Technologies, 2025)
IntroductionApart from discussing general issues related to the application of freeform telescopes, this work presents a design of ultra-compact high-resolution freeform telescope dedicated to CubeSat application associated with Earth surface imaging from Low Earth Orbit (LEO), providing high resolution (Ground Sampling Distance, GSD <5 m) and 20 km width of the observed Earth strip.MethodsThe telescope was designed in a three-mirror off-axis configuration according to the <0.5U volume constraint. Freeform surfaces were described by shifted polynomial equations. In order to prevent optimization falling into numerous local minima of multi-variate merit function, the new design strategy was proposed. The optical design commercial software was supplemented by add-on responsible for dynamically modifying the set of variables in the loop during the optimization process.ResultsThe designed 250 mm f/4.9 telescope meets the assumed operational and volumetric criteria. It fits into the volume of 5 × 10 × 10 cm cuboid. It is diffraction limited across the whole (3o) field of view.DiscussionFreeform optics design technology was successfully applied to design a miniature space telescope. The proposed design algorithm proved to be computationally efficient. It enabled to obtain the excellent imaging of the designed telescope, which from mathematical perspective becomes a challenging multi-variable optimization task, unattainable with the standard optimization procedures included in the commercial optical design software.